SUMO-specific Isopeptidases Tuning Cardiac SUMOylation in Health and Disease - Hotz, Paul W.; Müller, Stefan; Mendler, Luca (Frontiers in Molecular Biosciences, 2021)
SUMOylation is a transient posttranslational modification with small-ubiquitin like modifiers (SUMO1, SUMO2 and SUMO3) covalently attached to their target-proteins via a multi-step enzymatic cascade. SUMOylation modifies protein-protein interactions, enzymatic-activity or chromatin binding in a multitude of key cellular processes, acting as a highly dynamic molecular switch. To guarantee the rapid kinetics, SUMO target-proteins are kept in a tightly controlled equilibrium of SUMOylation and deSUMOylation. DeSUMOylation is maintained by the SUMO-specific proteases, predominantly of the SENP family. SENP1 and SENP2 represent family members tuning SUMOylation status of all three SUMO isoforms, while SENP3 and SENP5 are dedicated to detach mainly SUMO2/3 from its substrates. SENP6 and SENP7 cleave polySUMO2/3 chains thereby countering the SUMO-targeted-Ubiquitin-Ligase (StUbL) pathway. Several biochemical studies pinpoint towards the SENPs as critical enzymes to control balanced SUMOylation/deSUMOylation in cardiovascular health and disease. This study aims to review the current knowledge about the SUMO-specific proteases in the heart and provides an integrated view of cardiac functions of the deSUMOylating enzymes under physiological and pathological conditions.